Modifying platelets at their birth: anti-thrombotic therapy without haemorrhage - Feely, Conor; Kaushal, Nitika; D’Avino, Pier Paolo; Martin, John (Frontiers in Pharmacology, 2024)
Cardiovascular disease is a leading cause of death. The current approach to the preven4on of arterial thrombosis in cardiovascular disease is dependent on the use of therapies which inhibit the ac4va4on of platelets. Predictably these are associated with an increased risk of haemorrhage which causes significant morbidity. The thrombo4c poten4al of an ac4vated platelet is modifiable; being determined before thrombopoiesis. Increased megakaryocyte ploidy is associated with larger and more ac4ve platelets carrying an increased risk of thrombosis. The reduc4on in the ploidy of megakaryocytes is therefore a novel area of therapeu4c interest for reducing thrombosis. We propose a new therapeu4c approach for the preven4on and treatment of thrombosis by targe4ng the reduc4on in ploidy of megakaryocytes. We examine the role of a receptor mediated event causing megakaryocytes to increase ploidy, the poten4al for targe4ng the molecular mechanisms underpinning megakaryocyte endomitosis and the existence of two separate regulatory pathways to maintain haemostasis by altering the thrombo4c poten4al of platelets as targets for novel therapeu4c approaches producing haemosta4cally competent platelets which are not prothrombo4c.